PENAMBAHAN SENAM OTAK PADA PROGRAM SKJ 2008 LEBIH MENINGKATKAN KOORDINASI ANTARA MATA DAN TANGAN DARIPADA SKJ 2008 - Aniswatun Khasanah, al um; Pangkahila, J.Alex; Irfan, Muh. (Sport and Fitness Journal; Volume 4, No. 2, 2016)
Children in 7-8 years, the kinesthetic intelligence was more necessary incognitive development phase. Its indicated by the activities of chuildren’s motion suchas coordination between eye and hand. Gymnastics is a serial of simple physical activitywhich helps to optimize the brain function, one of them is coordination. This study wasconducted to determine how much improvement the addition of brain gym at SKJ 2008program to increase the coordination between eye and hand of children in age 7-8 years old. This study used an experimental method. It used the control group by using a studydesign two group pre and posttest control group design. This study was conducted at SDNegeri 3 Sumberjo Central Lampung, the training sessions were given 3 times during 6weeks. The number of samples was 36 children were divided into two groups. Thecontrol group was SKJ 2008 program however in the treatment group was given theaddition of brain gym in SKJ 2008 program. The tool used the wall toss test to measurethe eye and hand coordination which was conducted pre-intervention and postintervention.The results of test used independent t-test to determine eye and handcoordination. From the test was obtained the result that the increasing of eye and handcoordination in the mean post-intervention of group treatment was 7,06 ± 1,63 whichwas compared with control group was 4,44 ± 1,15 with p value = 0,000 (p <0,05). Theaddition of brain gym on SKJ 2008 program was more increasing the coordinationbetween eye and hand of children in age 7-8 years old in sd negeri 3 sumberjo at centrallampung.
Keywords: Brain Gym, Eye and hand Coordination, SKJ 2008 program